Economic stress and low leisure-time physical activity: Two life course hypotheses - Martin Lindström; Maria Rosvall (Elsevier, 2018)
The aim was to investigate associations between economic stress in childhood and adulthood, and low leisure-time physical activity (LTPA) in adulthood from two life course perspectives. The public health survey in Scania in the southernmost part of Sweden in 2012 is a cross-sectional study based on a stratified random sample with 28,029 respondents aged 18-80 (51.7% response rate). Associations between childhood and adult economic stress, and low LTPA were analyzed with logistic regressions. A 14.8% prevalence of men and 13.5% of women had low LTPA (sedentary lifestyle). Low LTPA was associated with higher age, being born abroad, low socioeconomic status, low trust, smoking, poor self-rated health, and economic stress in childhood and adulthood. The odds ratios of low LTPA increased with more accumulated economic stress across the life course in a dose-response relationship. There was no specific critical period (childhood or adulthood), because economic stress in childhood and adulthood were both associated with low LTPA but the associations were attenuated after the introduction of smoking and self-rated health. The accumulation hypothesis was supported because the odds ratios of low LTPA indicated a graded response to life course economic stress. The critical period hypothesis was thus not supported. Economic stress across the life course seems to be associated with low LTPA in adulthood. Keywords: Economic stress, Leisure-time physical activity, Accumulation, Critical period, Social capital, Sweden